2012
DOI: 10.1371/journal.pone.0040215
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Attention Modulates Pain Perception: An ERP Study

Abstract: IntroductionResearch has shown that people with chronic pain have difficulty directing their attention away from pain. A mental strategy that incorporates focused attention and distraction has been found to modulate the perception of pain intensity. That strategy involves placing attention on the nociceptive stimulus felt and shifting attention to a self-generated sub-nociceptive image and rehearsing it. Event-related potential was used to study the possible processes associated with the focus-then-orient stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 61 publications
3
35
1
Order By: Relevance
“…Both participants then underwent a psychophysical pain calibration procedure (similar to the one used in ref. 49). This process enabled us to determine reliable values for painful and nonpainful stimulation by asking participants to rate each stimulus on a seven-point scale ranging from 1 = "perceptible, but clearly nonpainful sensation" to 7 = "unbearable pain."…”
Section: Methodsmentioning
confidence: 99%
“…Both participants then underwent a psychophysical pain calibration procedure (similar to the one used in ref. 49). This process enabled us to determine reliable values for painful and nonpainful stimulation by asking participants to rate each stimulus on a seven-point scale ranging from 1 = "perceptible, but clearly nonpainful sensation" to 7 = "unbearable pain."…”
Section: Methodsmentioning
confidence: 99%
“…P3a is induced by novel or unexpected stimuli, while P3b is associated with context updating and subsequent memory storage (Coull, 1998;Polich, 2007). P600, sometimes referred to as late positive component or positive slow wave has been associated with several higher-level functions, including syntactic processing, item recognition and working memory capacity (Chan et al, 2012;Friedman and Johnson, 2000;Lefebvre et al, 2005;Mecklinger 2010;Swaab et al, 2012). We chose to analyze P3a, P3b, and P600 components.…”
Section: Visual Verbal Learning Testmentioning
confidence: 99%
“…In particular, focused attention and distraction enable the modulation of the perception of pain intensity . In (Chan et al, 2012) authors have shown that the brain enables to shift attention to a self-generated sub-nociceptive image and to rehearse it. Event-related potentials were used to study the possible processes associated with a focus-then-orient attention strategy.…”
Section: Attention -Pain Interactionmentioning
confidence: 99%